Effect of heat-clearing and dampness-eliminating Chinese medicine for high-risk cervical cancer papillomavirus infection: a systematic review and meta-analysis of randomized controlled trials - Huang, Shan; Qi, Yuanjie; Chen, Shouzhen; He, Baochang; Chen, Xueli; Xu, Jinbang (Frontiers in Medicine, 2023)
Background : Heat-clearing and dampness-eliminating Chinese medicine (HDCM) have been studied in clinical trials for cervical HPV infection for decades.However,there has been little comprehensive assessment of the strength and quality of evidence.We performed a systematic review and meta-analysis to assess the effectiveness and safety of HDCM in cervical high-risk HPV infected patients.Methods:The research focus questions were constructed in accordance with the Participants，Intervention，Comparison，and Outcomes(PICO) criteria，and a protocol was registered in PROSPERO. A comprehensive systematic search in eight electronic databases was conducted from the inception dates to June 30，2022.We then performed a systematic review and meta-analysis of all randomized controlled trials(RCTs) assessing the HDCM therapy methods.Results: A total of 12 studies were eligible for inclusion,including 1574 patients.The data synthesis showed that the HPV clearance rate of HDCM groups was superior to Interferon and follow-up groups(RR=1.4 0，95% CI:1.15,1.71，P<0.01) and (RR=3.15，95% CI:2.43,4.08，P<0.01), respectively.HDCM has greater potential in reducing HPV-DNA virus load(MD=-5.16,95% CI:-5.91,-4.41,P<0.01).The reversal rate of cervical intraepithelial neoplasia(CIN) for HDCM groups was approximately 2.8 times(RR=2.80,95% CI:2.19,3.57 ,P<0.01) as much as the follow-up groups.Additionally，the recurrence rate of HR-HPV at the end of follow-up period in this meta-analysis was reported to be lower in HDCM groups compared to follow-up groups[6.81%(16/235) and 14.65%(29/ 198),respectively]. The following Chinese herbal remedies were most common used：Huangbai( Phellodendron chinense var.Glabriusculum C.K. Schneid.),Kushen(Sophora flavescens Aiton),Daqingye(Isatis indigotica Fortune)，Zicao(Arnebia hi-spidissima DC.)，Baihuasheshecao(Hedyotis diffusa Spreng.)，Banlangen( Isatis tinctoria subsp.tinctoria L.)， Huzhang(Reynoutria japonica Hou-tt.)，Huangqi(Orobanche astragali Mouterde). Conclusion:HDCM interventions appears to have significant effects on enhancing the rate of HR-HPV clearance,reducing the HPV-DNA virus load,as well as increasing the regression rate of CIN. Some active components are responsible for this efficacy and worth further exploring.